Cloud climatologies from global climate models - a comparison of CMIP5 and CMIP6 models with satellite data - Lauer, Axel; Bock, Lisa; Hassler, Birgit; Schröder, Marc; Stengel, Martin (Journal of Climate, 2023)
Simulating clouds with global climate models is challenging as relevant physics involves many non-linear processes covering a wide range of spatial and temporal scales. As key components of the hydrological cycle and the climate system, an evaluation of clouds from models used for climate projections is an important prerequisite for assessing the confidence in the results from these models. Here, we compare output from models contributing to Phase 6 of the Coupled Model Intercomparison Project (CMIP6) with satellite data and with results from their predecessors (CMIP5). We use multi-product reference datasets to estimate the observational uncertainties associated with different sensors and with internal variability on a per-pixel basis. Selected cloud properties are also analyzed by region and by dynamical regime and thermodynamic conditions. Our results show that for parameters such as total cloud cover, cloud water path and cloud radiative effect, the CMIP6 multi-model mean performs slightly better than the CMIP5 ensemble mean in terms of mean bias, pattern correlation and relative root-mean square deviation. The inter-model spread in CMIP6, however, is not reduced compared to CMIP5. Compared with CALIPSO-ICECLOUD data, the CMIP5/6 models overestimate cloud ice particularly in the lower and middle troposphere partly due to too high ice fractions for given temperatures. This bias is reduced in the CMIP6 multi-model mean. While many known biases such as an underestimation in cloud cover in stratocumulus regions remain in CMIP6, we find that the CMIP5 problem of too few but too reflective clouds over the Southern Ocean is significantly improved.